A comprehensive analysis of the epidemiological and genomic characteristics of global Serratia Marcescens - Wenqin Chen; Zheqian Li; Jie Zheng; Danwei Wang; Shuo Gao; Wanqing Zhou; Han Shen; Yan Zhang; Xiaoli Cao (Journal of Global Antimicrobial Resistance)
Background: Serratia marcescens outbreaks present significant challenges in clinical treatment, necessitating a deeper understanding of its epidemiological and genomic traits. Objective: To analyse the epidemiological and genomic characteristics of S. marcescens at a global scale. Methods: High-quality genomes of S. marcescens were retrieved from NCBI and annotated using Prodigal. Antibiotic resistance genes (ARGs) were identified via Blastn, sequence types (STs) were determined with a proprietary tool, and phylogenetic analysis was conducted to explore evolutionary relationships. Results: The study analysed genomes from 33 countries, with major contributions from the USA (27.8%), UK (15.3%), Italy (14.7%), and Japan (10.7%). Human clinical samples accounted for 73.5% of the isolates, primarily from blood (44.8%) and sputum (19.3%). Eleven ARGs were identified, with sde being the most prevalent. Carbapenemase genes included blaSME, blaKPC, and blaNDM-1, though co-occurrence in individual strains was absent. Novel ARGs, including armA, rmtC, and fosA7.2, were reported. Among 855 genomes with identified STs, ST366, ST367, ST365, and ST423 were most common. Phylogenetic analysis highlighted significant genetic diversity and distinct evolutionary lineages. Conclusion: Temporal analysis showed a genome peak in 2019, underscoring the global prevalence and adaptability of S. marcescens. The distribution of ARGs across diverse STs emphasizes horizontal gene transfer as a key driver of resistance. Judicious antibiotic use is essential to mitigate further resistance.